SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN ORGANISASI MAHASISWA TERBAIK DI UPN VETERAN JAKARTA MENGGUNAKAN METODE MOORA (MULTI-OBJECTIVE OPTIMIZATION ON THE BASIS OF RATIO ANALYSIS) - Annisa Novaguinea, (2023)
UPN Veteran Jakarta has more than 90 student organizations, both in academic and non-academic. Each organization has their own vision that is aimed at student achievement and making UPN Veteran Jakarta proud. To achieve those achievements, there is a need in increase the quality of each organization by monitoring and evaluating so that organizations have better targets not only between periods but also between organizations in UPN Veteran Jakarta. The objective of this research is to create a decision support system for Best ORMAWA (Student Organizations) in UPN Veteran Jakarta in accordance with predetermined criteria. Assessment criteria that have been used before are divided into three categories, that is administrative and financial order, achievement and creativity ORMAWA, and established cooperation ORMAWA. Each category has assessment criteria and in total there are 32 assessment criteria. The method used in this decision support system is the MOORA (Multi-Objective Optimization on The Basis of Ratio Analysis) method. This method is chosen with consideration that this method calculates weighted criteria and non-weighted criteria so that later the system can be more flexible for set the rating. The result of this research is the website SISPEMAWA (Decision Support System for Best ORMAWA).